Alzheimer’s Disease Mutant Mice Exhibit Reduced Brain Tissue Stiffness Compared to Wild-type Mice in both Normoxia and following Intermittent Hypoxia Mimicking Sleep Apnea - Menal, Maria José; Jorba, Ignasi; Torres, Marta; Montserrat, Josep M.; Gozal, David; Colell, Anna; Piñol-Ripoll, Gerard; Navajas, Daniel; Almendros, Isaac; Farré, Ramon (Frontiers in Neurology, 2018)
BACKGROUND: Evidence from patients and animal models suggests that obstructive sleep apnea (OSA) may increase the risk of Alzheimer´s disease (AD) and that AD is associated with reduced brain tissue stiffness. AIM: To investigate whether intermittent hypoxia (IH) alters brain cortex tissue stiffness in AD mutant mice exposed to IH mimicking OSA. METHODS: Six-eight month old (B6C3-Tg(APPswe,PSEN1dE9)85Dbo/J) AD mutant mice and wild type (WT) littermates were subjected to IH (21% O2 40s – 5% O2 20s; 6 h/day) or normoxia for 8 weeks. After euthanasia, the stiffness (E) of 200-μ brain cortex slices was measured by Atomic Force Microscopy. RESULTS: Two-way ANOVA indicated significant cortical softening and weight increase in AD mice compared to WT littermates, but no significant effects of IH on cortical stiffness and weight were detected. In addition, reduced myelin was apparent in AD (vs. WT), but no significant differences emerged in the cortex extracellular matrix components laminin and glycosaminoglycans when comparing baseline AD and WT mice. CONCLUSION: AD mutant mice exhibit reduced brain tissue stiffness following both normoxia and intermittent hypoxia mimicking sleep apnea, and such differences are commensurate with increased edema and demyelination in AD.